Pictures & Paranoia. - Drimmer, Sonja (Art in America)
The author explores how art historians may help alleviate the paranoia brought by manipulated digital images that have been generated using artificial intelligence (AI) technology. Topics discussed include the increasing use of AI to create images that may be used for fraud and political disinformation, the signs of fabricated images such as spatial warping and blurring, and the techniques being used by art historians to authenticate artworks.